Angioplastia para trombose venosa profunda: revisão sistemática cochrane - Flumignan, Ronald Luiz Gomes [UNIFESP] (2016)
Objectives: To evaluate the effectiveness and safety of angioplasty (with or without stent) alone or more anticoagulation or more anticoagulation and thrombolysis in treating people with deep venous thrombosis, acute or chronic, through a Cochrane systematic review. Method: It was utilized the recommended Cochrane method. All randomized controlled trials that have examined angioplasty for deep venous thrombosis, along the lines of the objectives were considered. Searches were carried out in specialized register, the Cochrane Register of Studies and on the basis ?Literatura Latino Americana e do Caribe em Ciências da Saúde? e ?Indice Bibliográfico Español de Ciencias de la Salud?. References of the included studies were checked for other relevant studies. Experts, manufacturers and the authors of the included studies were contacted for any unpublished data. Participants who have received any form of mechanical thrombectomy were excluded. Two reviewers selected and extracted data from the studies independently. A third reviewer was consulted in case of disagreements. Results: Of the 12 pre-specified comparisons, only one [angioplasty (with or without stent) plus thrombolysis and best medical practice against best medical practice and thrombolysis] was identified for acute deep venous thrombosis. In both included studies (238 participants) thrombolysis was catheter-directed performed in the two groups: control and angioplasty. At 24 months, there was no difference in the incidence of venous thromboembolism and post-thrombotic syndrome. The most marked effects with angioplasty were seen in improving secondary patency (angioplasty group), which results in both periods early (12 months follow-up) and intermediate (24 months) showed significant differences. There were no cases of death or major bleeding and there was no difference in quality of life between the study arms (intermediate). The quality of the evidence, at 24 months of follow-up is moderate [lowered by indirectness (post-thrombotic syndrome) and imprecision (venous thromboembolism)]. Conclusions: This is the first systematic review of randomized controlled trials that with moderate-quality evidence suggests that angioplasty (with or without stent) offers potential advantages over standard treatment of deep venous thrombosis, through improved patency rate, without additional risk such as mortality, pulmonary embolism, major bleeding or recurrent DVT, even without significant improvement in quality of life and post-thrombotic syndrome in 24 months of follow-up.